'A real revolution': Ireland and the Oxford Group/Moral Re-Armament movement, 1933–2001. Issue 168 (November 2021) - Whelan, Bernadette
Abstract: During the twentieth century, Ireland, north and south, was infiltrated to varying degrees by a transnational quasi-religious and political movement, Moral Re-Armament (M.R.A.). From its founding in the early 1920s by an American evangelist and former Lutheran pastor, Frank Buchman, through the peak of moral revivalism in the 1930s, its Cold War work after 1945 and its reinvention as a secular, multi-faith, reconciliation organisation in the 1960s, this article examines M.R.A.'s structural and ideological origins and its evolution in Ireland, the U.S. and Britain. Based on primary source materials, it argues that Ireland, characterised by two ideologically narrow cultural and political monoliths, was not immune to external spiritual and quasi-political influences and that M.R.A.'s activities in Ireland confirm these distinctive religious and political cultures while also revealing similarities. Moreover, it reveals that non-governmental M.R.A. adherents were in advance of governments in their desire for peaceful solutions to the Irish partition issue and the Cold War more generally. The article, therefore, examines an international movement which had personal, national and global significance within the context of transnational religious, political and foreign policy studies as well as the national narratives of Northern Ireland and Ireland.